Contrasting realities: Italian advertisements and non-sexist linguistic and social norms / Piermauro Catarinella … [et al.] - Catarinella, Piermauro; Kram, Suhardi; Colombo, Omar; Husain, Muhammad Alhakeem (Faculty of Art and Design, 2024)
This research aims to scrutinise whether sexism is confined solely to the Italian advertising domain or extends into the language employed by the general populace and the broader cultural fabric of society. In Italy, despite numerous efforts made over the past decades to eradicate sexism in advertising campaigns, marketers frequently resort to its various manifestations, deeming it a powerful tool for attracting potential consumers. The prevalent utilisation of the female image in a sexist manner, portraying women as objects of desire, remains commonplace. Surprisingly, even renowned influencers aligned with the radical feminist movement often incorporate such tactics in their social media content. Sexism manifests through two principal avenues: firstly, the erotic portrayal of women’s bodies and/or their sensual behaviours, frequently coupled with language expressions encompassing with dual meanings; secondly, the perpetuation and reinforcement of stereotypical gender roles. While the latter has largely diminished in the contemporary era, the former persists prominently. This case study research employs a qualitative analysis approach. Various data sources, including legal documents, historical records, and contemporary media, are critically analysed. The findings suggest that, despite the societal and linguistic rejection of sexism in contemporary Italy, where gender equality prevails across social, economic, and legal realms, the advertising industry continues to rely on such practices heavily.